Biometrics and research methods teaching resource - International Livestock Research Institute (International Livestock Research Institute, 2013)
The aim of this electronic "Biometrics and Research Methods Teaching Resource" is to enhance effective teaching of and training in biometry through teaching guides, interactive, illuminating real-life case studies and other teaching materials. It is built around six proposed teaching guides that take the reader through the research process. These are - Research Strategy, Study Design, Data Management, Exploration & Description, Statistical Modelling and Reporting. The Teaching Resource also includes other teaching material provided from University of Reading, ICRAF, University of Kwazu-Natal and Massey University, New Zealand. The teaching resource contains 13 case studies drawn from research conducted in Ethiopia, Kenya, Swaziland, Uganda and Zambia. The case studies go through different parts of the research process as set out in the teaching guides, and illustrate how methods of design and analysis are applied to the examples described. Four short videos have also been produced that demonstrate how arable and animal experiments are laid out and illustrate other aspects of research methodology in the field. A fifth video shows a consultation between a biometrician and a client. Each case study has its own data set(s) and study questions and has been designed around the statistical software GenStat. A 'Discovery' version of GenStat, free to users in sub-Saharan Africa, is distributed alongside this teaching resource.